A Study on Jobaru River Basin Management by Numerical Simulations of Flooding and Sediment Deposition with Field Survey - K. Ohgushi; H. Nakashima; T. Hino; T. Morita; T. Jansen (International Association of Lowland Technology, 2016)
River basin management in Japan in the early modern period can be considered as providing a prototype of possible countermeasures for present-day flood exceeding the design level. The river basin management in the Saga region of Japan was established by Naritomi Hyogo in the early Edo era. This study evaluates characteristics of river basin management in Jobaru River Basin located in the eastern Saga Plain using numerical simulations and geotechnical surveys. A flood flow of Jobaru River was calculated using a 1-D flow numerical simulation. Overflow discharges from Nokoshi, open levee and no-levee intervals are estimated and these discharges are specified as boundary conditions for quasi 3-D inundation flow simulations. 2-D sediment transport by water flow is also simulated. A Geoslicer is used for field surveys that uncover clues of how the sediment has been deposited in the past. The ages of the sampled stratums was measured by using radiocarbon dating methods. The classified sediments columns and estimated ages of the stratum by the radiocarbon dating correspond to the simulated flood flow behavior in the retarding basin after overflow from the Nokoshi and open levee. Moreover, No.1 open levee reproduced by the geotechnical survey's result is used for the flow simulation successfully.